2018
DOI: 10.3390/v10100574
|View full text |Cite
|
Sign up to set email alerts
|

Improved Baculovirus Vectors for Transduction and Gene Expression in Human Pancreatic Islet Cells

Abstract: Pancreatic islet transplantation is a promising treatment for type 1 diabetes mellitus offering improved glycaemic control by restoring insulin production. Improved human pancreatic islet isolation has led to higher islet transplantation success. However, as many as 50% of islets are lost after transplantation due to immune responses and cellular injury, gene therapy presents a novel strategy to protect pancreatic islets for improved survival post-transplantation. To date, most of the vectors used in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Thus, several investigations have been reported that have offered improvements in baculoviral vectors for BacMamtype applications. In this, list of developments can be mentioned: (i) the pseudo-typed BVs, which constructs express in insect cells the stomatitis-vesicular-virus glycoprotein (Barsoum et al 1997;Kolangath et al 2014) or other factors from eukaryote parasites and viruses (Tamura et al 2016;Hu et al 2019a) to increase transduction capability in mammals; (ii) the development of baculoviral-hybrid vectors that achieve a longer duration of the GOI expression by, for example, the presence of the ORI P of the Epstein-Barr virus, either alone (Shan et al 2006;Suzuki et al 2009) or combined with the FLP/FRP, ɸC31/attB-P or Cre/Loxp recombinase systems (Lo et al 2009(Lo et al , 2017Sung et al 2013); (iii) the inclusion of the inverted terminal repeats and the Rep gene of the adeno-associated virus (Wang 2008) or the inverted terminal repeats and the transposase gene of the Sleeping-Beauty transposon et al 2014); and (iv) genome modifications to increase the BV yield in insect cells (Graves et al 2018), among other optimizations. In addition, progress has been made in different formulations to achieve better results after the administration of recBVs in mammals.…”
Section: Bacmam Technology Associated With Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several investigations have been reported that have offered improvements in baculoviral vectors for BacMamtype applications. In this, list of developments can be mentioned: (i) the pseudo-typed BVs, which constructs express in insect cells the stomatitis-vesicular-virus glycoprotein (Barsoum et al 1997;Kolangath et al 2014) or other factors from eukaryote parasites and viruses (Tamura et al 2016;Hu et al 2019a) to increase transduction capability in mammals; (ii) the development of baculoviral-hybrid vectors that achieve a longer duration of the GOI expression by, for example, the presence of the ORI P of the Epstein-Barr virus, either alone (Shan et al 2006;Suzuki et al 2009) or combined with the FLP/FRP, ɸC31/attB-P or Cre/Loxp recombinase systems (Lo et al 2009(Lo et al , 2017Sung et al 2013); (iii) the inclusion of the inverted terminal repeats and the Rep gene of the adeno-associated virus (Wang 2008) or the inverted terminal repeats and the transposase gene of the Sleeping-Beauty transposon et al 2014); and (iv) genome modifications to increase the BV yield in insect cells (Graves et al 2018), among other optimizations. In addition, progress has been made in different formulations to achieve better results after the administration of recBVs in mammals.…”
Section: Bacmam Technology Associated With Gene Therapymentioning
confidence: 99%
“…We need to mention that certain studies were carried out in nonhuman primates (Balasundaram et al 2017) or using whole-human-blood samples (Georgopoulos et al 2009) and cells from human donors (Bak et al 2011;Paul et al 2011;Graves et al 2018;Wang et al 2019aWang et al , 2020. In addition, owing to the excellent transport capability of baculoviruses, new approaches in synthetic biology are being explored in vitro that enable, for example, the incorporation of complex gene circuits that can express a therapeutic gene in target cells and not in others (Lin et al 2018).…”
Section: Bacmam Technology Associated With Gene Therapymentioning
confidence: 99%
“…Many exogenous membrane proteins can be functionally displayed on the baculovirus envelope during virus assembly and budding. It is reported that the vesicular stomatitis virus glycoprotein G (VSV-G) protein displayed on baculovirus envelope can enhance the infectivity of baculovirus towards mammalian cells 13 and a short fragment of VSV-G (VSV-GED) is sufficient to facilitate baculovirus-mediated gene delivery in vertebrate cells 14,15 . In order to trace the successful transfection of bacmid and production of baculovirus, we utilize the polyhedrin promoter to drive the expression of a fluorescent reporter, VSV-GED-LOV fusion protein in insect cells.…”
Section: Design Of the Pbmcl1 Vectormentioning
confidence: 99%
“…A GP64 signal peptide directs the fusion protein to the plasma membrane of insect cell and virus envelope. VSV-GED fragment is used to enhance the infectivity of baculovirus 14,15 . CreiLOV is a small, thermostable, photostable, and fast-maturing monomeric flavin-based green fluorescent protein 16…”
Section: Design Of the Pbmcl1 Vectormentioning
confidence: 99%
See 1 more Smart Citation